Evaluation the Mechanical Properties of Kaolin Particulate Reinforced Epoxy Composites - Mohmmed, Jabbar Hussein (Al-Khwarizmi Engineering Journal, 2018)
Epoxy resin has many chemical features and mechanical properties, but it has a small elongation at break, low impact strength and crack propagation resistance, i.e. it exhibits a brittle behavior. In the current study, the influence of adding kaolin with variable particle size on the mechanical properties (flexural modulus E, toughness Gc, fracture toughness Kc, hardness HB, and Wear rate WR) of epoxy resin was evaluated. Composites of epoxy with varying concentrations (0, 10, 20, 30, 40 weights %) of kaolin were prepared by hand-out method. The composites showed improved (E, Gc, Kc, HB, and WR) properties with the addition of filler. Also, similar results were observed with the decrease in particle size. In addition, in this study, multiple regression models were developed by utilizing (SPSS) package to predict the properties of kaolin reinforced epoxy composites. Good agreement was obtained between the predicted and the experimental results. The accuracy of prediction was (89.71%, 80.58%, 85.82%, 92.27%, and 94.49%) for E, Gc, Kc, HB, and WR, respectively.